PERAN ORANG TUA DAN PERILAKU SISWA DENGAN KEJADIAN KARIES GIGI PADA SISWA KELAS V SD DI WILAYAH KERJA PUSKESMAS BANGLI TAHUN 2019 - Ni Nyoman Dewi Supariani; Ni Made Sirat; Asep Arifin Senjaya (Jurnal Kesehatan Gigi (Dental Health Journal), 2023)
Indonesia there was an increase in the prevalence of dental caries in the Indonesian population in 2007, from 43.4% to 53.2% in 2013. Riskesdas 2018 data recorded the proportion of dental and mouth problems in Indonesia at 57.6%. that, the population with dental and mouth problems in the last 12 months in Bali is 24.0% and the highest is in Bangli Regency, which is 41.5%. The purpose of this study was to analyze the relationship between the role of parents and students with the incidence of dental caries in fifth grade students of elementary schools in the work area of Bangli Health Center in 2019. The samples of this study were all fifth grade students of the Bangli Community Health Center working area. Quantitative data analysis is done univariately, in the form of frequencies and percentages. Bivariate analysis with cross tabulation and Spearmen's correlation test. The results of this study were obtained by students mostly caries in the very low category 146 people (58.45%) . The most dental and oral hygiene with medium categories were 161 people (64.45%), the role of parents in the oral and dental hygiene with the most categories was 173 people (69.2%). The relationship of the role of parents with caries incidence obtained sig.0.546 ( 0.05) means that there is no relationship between the role of parents with caries incidence.The relationship of dental and oral hygiene with dental caries and mouth events obtained sig. 0.161 (0.05) means that there is no significant relationship between dental and oral hygiene with the incidence of dental caries.The conclusion of this study is the highest dental caries in children with a very low caries category that is as much as 58.4%, the role of parents in oral and dental hygiene with the most roles category is as many as 173 people (69.2%), the most dental and oral hygiene of students with a medium category of 161 people (64.4%), there was no relationship between the role of parents with the caries incidence of Grade V students of SDN in the Bangli Health Center area, there was no relationship between dental and oral hygiene with the incidence of dental caries of  Grade V SDN students in the Bangli Health Center area.